2009
DOI: 10.1111/j.1600-0404.1994.tb02753.x
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesions and cognitive deficits: relevance of lesion pattern?

Abstract: Magnetic resonance imaging (MRI) permits efficient visualization of white matter lesions (WML). A growing body of literature deals with the correlation of WML and cognitive dysfunction with conflicting results. We studied the influence of lesion pattern as well as size by analyzing MRI and psychometric test performance in 2 patient collectives with different WML patterns. 22 patients with myotonic dystrophy (MD) and mainly subcortical WML werecompared with 39 patients with multiple sclerosis (MS) and mainly pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 28 publications
4
16
0
2
Order By: Relevance
“…Some authors do not find a clinical correlate to the neuroimaging profile, 14 whereas others find a correlation between neuropsychological data and the distribution and severity of white matter abnormalities. 24,45,111 We found no correlation between the degree of cerebral involvement on traditional MRI studies and cognitive and behavioral profiles. 72 Other authors suggest an evolution of white matter abnormalities during the disease.…”
Section: Neuroimaging Evidencementioning
confidence: 54%
See 3 more Smart Citations
“…Some authors do not find a clinical correlate to the neuroimaging profile, 14 whereas others find a correlation between neuropsychological data and the distribution and severity of white matter abnormalities. 24,45,111 We found no correlation between the degree of cerebral involvement on traditional MRI studies and cognitive and behavioral profiles. 72 Other authors suggest an evolution of white matter abnormalities during the disease.…”
Section: Neuroimaging Evidencementioning
confidence: 54%
“…Several authors tried to correlate neuropsychological and neuroimaging findings. 6,24,27,28,45,62,101 Meola et al 71,72 confirmed a selective impairment on tests of frontal lobe function in DM1 and suggested that this type of deficit does not correlate with cortical atrophy and white matter hyperintense lesions, but might be associated with fronto-temporal lobe hypoperfusion on PET studies.…”
Section: Global Intelligencementioning
confidence: 84%
See 2 more Smart Citations
“…Neuropsychological studies has shown especially executive functions on frontal lobe has been deterioted at DM1 2 . While on imaging studies with magnetic resonance imaging (MRI) brain atrophy is detected at particularly anterior temporal lobe 3 , on brain positron emission tomography (PET) studies hypometabolism was observed on frontal and temporal lobes 4,5 . Also intraneural neurofibrillary tangles and tau protein accumulation in DM1 were same as frontotemporal dementia on pathological studies 6 .…”
Section: Introductionmentioning
confidence: 99%